Sex differences in hippocampal response to endocannabinoids after exposure to severe stress. Issue 7 (15th March 2016) - Zer‐Aviv, Tomer Mizrachi; Akirav, Irit
ABSTRACT: Women are more vulnerable to stress‐related mental disorders than men and the naturally occurring fluctuation in estrogen that occur across the estrus cycle can dramatically influence the pathophysiology observed following traumatic events. It has been demonstrated that the endocannabinoid (eCB) system could represent a therapeutic target for the treatment of post‐traumatic stress disorder (PTSD) in males. The current study aimed to examine the effects of exposure to a traumatic event and acute enhancement of eCB signaling on hippocampal‐dependent learning and plasticity in male and female rats. Males and females were exposed to the single prolonged stress (SPS) model of PTSD (restraint, forced swim, and sedation) followed by acute administration of the fatty acid amide hydrolase (FAAH) inhibitor URB597 (0.3 mg/kg). Females were in diestrus during SPS exposure. SPS exposure impaired extinction and hippocampal plasticity tested a week later in males and females. Sex differences were observed in the effects of URB597 on hippocampal plasticity of SPS‐exposed rats. Also, URB597 normalized the SPS‐induced upregulation in CB1 receptor levels in the amygdala, prefrontal cortex (PFC), and hippocampus in males. In females, URB597 normalized the SPS‐induced up regulation in CB1 receptors in the amygdala and PFC, but not hippocampus. Our findings support the eCB system as a therapeutic target for the treatment of disorders associated to inefficient fear coping in males and females. There are differences in the hippocampal response of males and females to the enhancement of eCB signaling after intense stress suggesting sex differences in treatment efficacy. © 2016 Wiley Periodicals, Inc.